2020
DOI: 10.3390/su12187502
|View full text |Cite
|
Sign up to set email alerts
|

Do Spanish Students Become More Sustainable after the Implementation of Sustainable Practices by Universities?

Abstract: Higher Education Institutions (HEIs) are a critical component to develop and promote sustainable solutions for both society and the planet. A challenge to HEIs is to provide students with the knowledge and skills required to achieve Sustainable Development (SD), as they are important stakeholders. In order for a person to take responsibility for a sustainable future, it is not only important to implement SDs in higher education, but to follow the progress of the individuals’ awareness of the sustainable world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 49 publications
(114 reference statements)
3
19
0
Order By: Relevance
“…The results concerning SD knowledge, as well as available literature, confirm the existence of an educational gap relating to economic and social SD aspects (Sandoval et al, 2020). The results concerning SD knowledge of medical university students seem to suggest that they possess elementary knowledge.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The results concerning SD knowledge, as well as available literature, confirm the existence of an educational gap relating to economic and social SD aspects (Sandoval et al, 2020). The results concerning SD knowledge of medical university students seem to suggest that they possess elementary knowledge.…”
Section: Discussionsupporting
confidence: 75%
“…Previous research confirms in-depth SD knowledge among students (Al-Naqbi and Alshannag, 2018;Esa, 2010;Tuncer, 2008). In addition, previous studies discuss differences in the knowledge and perception of SD as regards gender (Kagawa, 2007;Tuncer, 2008;Vicente et al, 2013) and faculties/ fields of study (Sandoval et al, 2020). Other variables have not been extensively studied (Al-Naqbi and Alshannag, 2018).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…They found that students majoring in environmental sciences have a higher knowledge relative to social science majors. In Europe, researchers found that faculties of science and engineering have the greatest changes in environmental attitudes and the highest level of sustainability knowledge based on a survey of 504 students from a Spanish university [11]. In the U.S., the authors of [12] studied students' awareness and attitudes at the University of Vermont and found a strong understanding of sustainability and that students consider sustainability to be important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Universities play an important role in integrating the basic goals of sustainability development in society [1]. They are contributors of new sustainable solutions for both society and the planet [2,3] and new knowledge such as sustainability [4]. Therefore, Education for Sustainability (EfS) in Higher Education (ESHE) has been increasing society's awareness and is a key enabler for sustainable development and an integral element of quality education [5].…”
Section: Introductionmentioning
confidence: 99%